2019
DOI: 10.1055/a-0826-1326
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diagnostic Hysteroscopy in the Evaluation of Fallopian Tube Patency: a Short Review

Abstract: The relevance of diagnostic hysteroscopy, especially when performed in an outpatient “office” setting, in the evaluation process of infertility has increased within the last few years. Notably, several articles on a possible role for diagnostic hysteroscopy in the assessment of Fallopian tube patency have been published recently. Three relevant articles were identified. Visualizing a “flow effect” or air bubbles dispersing through the ostia, sonographically assessed shifts in cul de sac volume, and selective F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Especially for an invasive procedure, it seems desirable to maximize the output of information. Notably, in the last few years, several studies have reported that diagnostic hysteroscopy could also play a possible role in tubal patency assessment [5]. This additional information might be of high relevance because tubal factors have been estimated to account for about 14% of all cases of female subfertility [6].…”
mentioning
confidence: 99%
“…Especially for an invasive procedure, it seems desirable to maximize the output of information. Notably, in the last few years, several studies have reported that diagnostic hysteroscopy could also play a possible role in tubal patency assessment [5]. This additional information might be of high relevance because tubal factors have been estimated to account for about 14% of all cases of female subfertility [6].…”
mentioning
confidence: 99%
“…As previously described for the office [7,10], combining disposable supplies with equipment depreciation amounted to $25 per procedure, which is comparable with the cost of catheters used for sonosalpingography and HSG. Another limitation to the present study relates to not precisely quantifying the laparoscopic pressures necessary to achieve tubal patency, particularly given that high-pressure patency is associated with lower fecundity than when it is observed with lower pressure [6,18]. However, this constraint is common to almost all publications on tubal patency.…”
Section: Discussionmentioning
confidence: 94%
“…Several approaches to hysteroscopic assessment of fallopian tubal patency exist and have been recently reviewed [6]. The 2 approaches with the highest potential seem to be the Parryscope and flow techniques, based on speed, cost, ease of learning, and gentleness (as they can be performed without an operative channel, allowing for smaller hysteroscopes).…”
mentioning
confidence: 99%
“…Hager et al [30] considered the use of diagnostic hysteroscopy in tubal patency evaluation extremely promising. In their conclusions, the authors raised a doubt about which technique should be considered the most accurate.…”
Section: Discussionmentioning
confidence: 99%